What have we learned about generic competitive strategy? A meta-analysis - Campbell-Hunt, Colin (Strategic management journal, 2000)
The dominant paradigm of competitive strategy is now nearly two decades old, but it has proved difficult to assess its adequacy as a descriptive system, or progress its propositions about the performance consequences of different strategic designs. It is argued that this is due to an inability to compare and cumulate empirical work in the field. A meta-analytic procedure is proposed by which the empirical record can be aggregated. Results suggest that, although cost and differentiation do act as high-level discriminators of competitive strategy designs, the paradigm's descriptions of competitive strategy should be enhanced, and that its theoretical proposition on the performance of designs has yet to be supported. A considerable agenda for further work suggests that competitive strategy research should recover something of its former salience.